Capacity enhancement of the indigenous Qur'anic schools in Somalia : an alternative model to deliver basic formal education - Warsame, Ali Abdalah (2006)
In any country, formal education plays a major, or even vital role in transforming the aspirations and needs of its people into reality. Somalia today, represents an underdeveloped nation where the state-run formal schooling system had once failed to provide basic education to the deprived nomadic peoples who constitute 60 percent of the population. Since the outbreak of Civil War in 1991, that formal schooling system had become almost non-existent. Yet, throughout its long history, the indigenous Qur'anic schools, with its few variations, continue to provide the necessary Islamic education to the children and young adults of the country. Given the setting, the overall aim of this case study is to look closely at the possibility of using the "Hybrid" Qur'anic School (HQS) system -- an indigenous institution that has remained largely intact and continued operating during this long conflict - as a viable alternative mode for providing access to formal basic education to a large number of children in urban and semi-urban centers.